Molecular phylogenetics and divergence dating of Byttnerioideae in Bangladesh using Matk DNA barcode (Journal of the Asiatic Society of Bangladesh, Science, 2026)
Byttnerioideae Burnett is an economically and medicinally important subfamily belonging to Malvaceae. A molecular phylogenetic and dating approach was undertaken to elucidate the evolutionary relationships and divergence history of the Byttnerioideae species available in Bangladesh based on the matK gene. A multifaceted, algorithm-driven strategy was applied with Maximum-Likelihood (ML), Maximum-Parsimony (MP), and Bayesian Inference (BI) algorithms that resulted in a consistent tree topology for the four tribes, namely as Byttnerieae, Hermannieae, Theobromateae and Lasiopetaleae. All the tribes exhibited monophyletic origin with strong bootstrap and posterior probability support. Byttnerieae, Hermannieae and Theobromateae were found to be more closely related to each other than to Lasiopetaleae. Molecular dating analysis revealed Lasiopetaleae as the oldest tribe, diverging approximately 39.51 million years ago (MYA) in the Bartonian age of the Cenozoic era, while Byttnerieae was identified as the most recent tribe, diverging around 33.24 MYA in the Rupelian age of the same era. These findings would update the phylogenetic relationship of Byttnerioideae and provide valuable insights for the development of the historical biogeography of Byttnerioideae in future endeavors.J. Asiat. Soc. Bangladesh, Sci. 51(2): 151-163, December 2025